1998
DOI: 10.1073/pnas.95.21.12663
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent corticofugal adjustment of midbrain frequency map in bat auditory system

Abstract: Recent studies of corticofugal modulation of auditory information processing indicate that cortical neurons mediate both a highly focused positive feedback to subcortical neurons ''matched'' in tuning to a particular acoustic parameter and a widespread lateral inhibition to ''unmatched'' subcortical neurons. This cortical function for the adjustment and improvement of subcortical information processing is called egocentric selection. Egocentric selection enhances the neural representation of frequently occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(147 citation statements)
references
References 45 publications
3
138
6
Order By: Relevance
“…It clarifies data about how bottom-up processing and learned tuning of adaptive filters is modulated by top-down attentive learned expectations that embody predictions or hypotheses that focus attention on expected bottom-up stimuli (Salin and Bullier, 1995;Engel et al, 2001;Gao and Suga, 1998;Krupa et al, 1999;Desimone, 1998;Ahissar and Hochstein, 2002;Hermann et al, 2004). These data support predictions of Adaptive Resonance Theory, or ART (Grossberg, 1980(Grossberg, , 2003Carpenter andGrossberg, 1987, 1993) that top-down expectations regulate predictive coding and matching and thereby help to focus attention, synchronize and gain-modulate attended feature representations, and trigger fast learning that is dynamically buffered against catastrophic forgetting.…”
Section: Figure 2 (A)mentioning
confidence: 69%
See 2 more Smart Citations
“…It clarifies data about how bottom-up processing and learned tuning of adaptive filters is modulated by top-down attentive learned expectations that embody predictions or hypotheses that focus attention on expected bottom-up stimuli (Salin and Bullier, 1995;Engel et al, 2001;Gao and Suga, 1998;Krupa et al, 1999;Desimone, 1998;Ahissar and Hochstein, 2002;Hermann et al, 2004). These data support predictions of Adaptive Resonance Theory, or ART (Grossberg, 1980(Grossberg, , 2003Carpenter andGrossberg, 1987, 1993) that top-down expectations regulate predictive coding and matching and thereby help to focus attention, synchronize and gain-modulate attended feature representations, and trigger fast learning that is dynamically buffered against catastrophic forgetting.…”
Section: Figure 2 (A)mentioning
confidence: 69%
“…Both V2→V1 feedback (Bullier et al, 1988) and V1→LGN feedback (Sillito et al, 1994) possess this structure. A similar modulatory on-center, offsurround architecture has been observed in feedback interactions from auditory cortex to the medial geniculate nucleus (MGN) and the inferior colliculus (IC) (Zhang et al, 2004;Gao and Suga, 1998). Consistent with the ART prediction of the role of attention in controlling adult plasticity, Gao and Suga (1998) found that acoustic stimuli caused plastic changes in the IC of bats only when the IC received top-down feedback from auditory cortex.…”
Section: 21mentioning
confidence: 71%
See 1 more Smart Citation
“…Subjects can become conditioned to temporal intervals and produce anticipatory learned behavioural responses to the time that a CS is scheduled, not to the CS itself. This is a potential problem in some recent studies of auditory cortical plasticity 25,52 . to the CS frequency increased relative to the pre-training BF over three days (72 hours) and then stabilized over ten days.…”
Section: Box 2 Melding Sensory Physiology and Learning/memorymentioning
confidence: 99%
“…Moreover, they report that collicular tuning shifts develop before auditory cortical shifts, although they disappear within about one hour whereas cortical shifts last at least 24 hours. Inactivation of the primary somatosensory cortex is reported to prevent cortical and collicular RF plasticity 25,52 . As reviewed above, the studies do not include validation of behavioural learning.…”
mentioning
confidence: 99%